The Political Geography of Distributive Politics. Issue 1 (February 2015) - Clemens, Austin C.; Crespin, Michael H.; Finocchiaro, Charles J.
<x xml:space="preserve">Abstract</x> Distributive politics plays an integral role in theories of legislative politics because it represents a fundamental aspect of legislators' electoral connection to constituents. We argue that because distributive politics is at its core a constituency‐centered process, it is essential to take geography into account in both substantive and statistical terms. Our analysis, which employs Geographic Weighted Regression, reveals substantial spatial heterogeneity in traditional models of pork‐barreling. The results challenge the implicit assumption that one size fits all when modeling the behavior of members of Congress in the realm of distributive politics.